INVESTIGATION OF STRESS IN PRIMATES MAINTAINED IN ZOO AND ITS MAIN IMPLICATIONS ON BEHAVIOR AND WELL-BEING (Veterinária Notícias, 2021)
Brazil is considered the country with the largest number of known primate species. Captive environments that do not have an environmental enrichment program are often easily discouraged with captive life, especially in zoos, and may develop a chronic stress condition. Objective: To raise, through an integrative review, the causes of stress in primates kept in zoos, focusing on the reactions resulting from these changes, as well as their implications on behavior and welfare. Methodology: Integrative literature review using the descriptors “Pathophysiology”, “Stress”, “Primates”, “Zoos” and “Wellness” in the main bases of scientific research. Results: Of 38 articles found, 30 were included. Conclusion: It is concluded that individual variations in behavioral profile expose primates differently to stressful conditions. At the zoo, visitation, lack of structure, shrinkage of the enclosure, poor nutritional management and an environment without stimuli can be potential sources of stress for some housed primates.Keywords: Pathophysiology; Stress; Primates; Zoos; Welfare.